Comparison of carbon-based nanomaterials characteristics on H13 tool steel: Vergleich der Eigenschaften Kohlenstoff-basierter Nanomaterialien auf H13 Werkzeugstahl - Emamian, S. (Wiley-VCH Verlag, 2017)
As the demand to weld higher strength materials through friction stir welding (FSW) increases, the need for better non-consumable rotating tool also increases as it has to be able to endure high frictional and thermal deformation while the work-piece undergoes intense plastic deformation at high temperatures. Carbon-based nanomaterials are good options to increase strength of steel. An attempt to improve the friction stir welding tool through carbon-based coatings on H13 tool steel has been carried out. This paper highlights the characterization of the carbon-based coatings in regard to selected coating parameters through Field emission scanning electron microscope, energy dispersive spectroscopy, Raman Spectra, and X-Ray photoelectron spectroscopy techniques. The analysis shows presence of graphite like structures whereas Carbon Nanotubes (CNT) was observed to be grown uniformly on the surface. © 2017 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim